Math, asked by foolbird2877, 1 year ago

If a xor b = c then show that a xor c = b and b xor c = a using boolean algebra

Answers

Answered by kansalanmol0609
23

Answer:

Simple proof!!

Step-by-step explanation:

a xor b = c

take xor with 'a' both side

a xor(a xor b) = a xor c

Now, we know a xor a = 0,

0 xor b = a xor c

or, we can say: -

b = a xor c

Answered by qwnerazzuri
4

Given:

a xor b = c

To Proof:

a xor c = b and

b xor c = a

Solution:

we have,

a xor b = c

taking  xor with 'a' both side

⇒  a xor(a xor b) = a xor c

⇒  (a xor a)* xor b) = a xor c

⇒  0 xor b = a xor c               (as, a xor a = 0)

⇒  a xor c = b

Again,

a xor b = c

taking  xor with 'b' both side

⇒  b xor(a xor b) = b xor c

⇒  (b xor a)* xor b) = b xor c

⇒  0 xor a = a xor c               (as, b xor b = 0)

⇒  a xor c = a

So, a xor c = b and b xor c = a  Proved.

Similar questions